Functional Effects of EPS-Producing Bifidobacterium Administration on Energy Metabolic Alterations of Diet-Induced Obese Mice - Salazar, Nuria; Neyrinck, Audrey M.; Bindels, Laure B.; Druart, Céline; Ruas-Madiedo, Patricia; Cani, Patrice D.; de los Reyes-Gavilán, Clara G.; Delzenne, Nathalie M. (Frontiers in Microbiology, 2019)
Obesity has been recognized by the World Health Organization as a global epidemic. The gut microbiota is considered as a factor involved in the regulation of numerous metabolic pathways by impacting different functions of the host. It has been suggested that probiotics can modulate host gene expression and metabolism, and thereby positively influence host adipose tissue development and obesity related-metabolic disorders. The aim of the present work was to evaluate the effect of an exopolysaccharide (EPS)-producing Bifidobacterium strain on host glucose and lipid metabolism and the gut microbial composition in a short-term diet-induced obesity in mice. C57BL/6J male mice were randomly divided into three groups: a control group that received control standard diet, a group fed a high-fat diet (HF) and a group fed high-fat diet supplemented with Bifidobacterium animalis IPLA R1. Fasting serum insulin as well as triglycerides accumulation in the liver were significantly reduced in the group receiving B. animalis IPLA R1. The treatment with the EPS-producing B. animalis IPLA R1 tended to down-regulate the expression of host genes involved in the hepatic synthesis of fatty acids which was concomitant with an increase in the expression of genes related with fatty acid oxidation. B. animalis IPLA R1 not only promoted the increase of Bifidobacterium but also the levels Bacteroides-Prevotella. Our data indicate that the EPS-producing Bifidobacterium IPLA R1 strain may have beneficial effects in metabolic disorders associated with obesity, by modulating the gut microbiota composition and promoting changes in lipids metabolism and glucose homeostasis.